STUDIES OF RADIATION PASTEURISATION OF MEDIUM FATTY FISH I. CONTROL OF RADIATION INDUCED OXIDATIVE CHANGES IN WHITE POMFRET (Stromateus cinereus) BY VACUUM PACKAGING - KAMAT, S V; KUMTA, U S (Fishery Technology, 2025)
Marked differences were observed in proximate biochemical compositions of the skin and muscle of white pomfret. The skin showed comparatively higher content of extractable lipids and was: more susceptible to radiation-induced oxidative changes like development of rancid odours and yellow discolouration than the muscle. Irradiation of skin samples under vacuum suppressed these changes.